Association of BDNF and MMP-9 single-nucleotide polymorphisms with the clinical phenotype of schizophrenia - Pan, Lihong; Cao, Zhonghai; Chen, Lianghu; Qian, Min; Yan, Yuzhong (Frontiers in Psychiatry, 2022)
Objective: Schizophrenia (SZ) is a severe chronic mental disorder and complex genetic mechanisms underlying the pathogenesis remains elusive. Brain-derived neurotrophic factor (BDNF) and matrix metalloproteinase 9 (MMP-9) is one of promising candidate genes for SZ. To shed some light on the association of BDNF and MMP-9 single-nucleotide polymorphisms with the clinical variability of SZ phenotype, the present study was designed to explore the relationship, and provide more conclusive evidence regarding their association with various clinical expression of SZ. Methods: A case-control association study was performed, and one hundred and five subjects of Chinese Han population were recruited, including 55 SZ patients and 50 healthy controls (HC). The BDNF rs6265 196 G>A and MMP-9 rs3918242 −1562C>T SNPs were genotyped using PCR-RFLP assay. Symptoms of schizophrenia were assessed using the Positive and Negative Syndrome Scale (PANSS). Results: A statistically significant difference was observed (P<0.01) with the patients carrying a significantly higher frequency of the BDNF rs6265 GG/GA genotypes and a lower frequency of the BDNF rs6265 AA genotype in comparison to HC. With regards to MMP-9 rs3918242 −1562C>T SNP, there was no significance between the control and SZ patients. BDNF GG genotype showed significantly higher PANSS (P<0.01) and positive symptoms score (P<0.01) than GA and AA genotypes. MMP-9 CC genotype showed significantly higher PANSS (P=0.03) and general score (P=0.02) than CT and TT genotypes. Conclusion: BDNF rs6265 196 G>A and MMP-9 rs3918242 −1562C>T SNPs are associated with the clinical phenotypes of SZ and may be a useful biomarker for the changes in clinical status, remission or exacerbation of SZ.